Processing of Seafood Into Contemporary Food That Is Nutritious And Economically Valuable In Welcoming Ecotourism In Nagari Kurai Taji, Nan Sabaris District, Padang Pariaman Regency - Fauzana - Gazali; Melindra Mulia; Trisna Kumala Sari; Umar Kalmar Nizar (Pelita Eksakta, 2021)
Nagari Kurai Taji is located in Nan Sabaris District, Padang Pariaman Regency, West Sumatra Province. This area is inhabited by 9335 people, most of whom work as fishermen, traders and farmers. Kurai Taji community who work as fishermen usually only sell their haul as raw materials or basic ingredients for cooking, so the profits are not much. The abundant marine haul is sometimes also difficult to sell to the public, especially in the midest of the current pandemic situation. In addition to fishing, the kurai taji peoples are also known as traders. They sell many things like daily necessities and Pariaman’s spesifics culinary. However, from the information obtained, there are not many people who sell contemporary foods that are liked by young people in this area, especially those processed from seafood. This community services aims to equiped the people in Kurai Taji Village with skills in processing seafood into modern food that is healthy, nutritious and has high economic value. After participating in the training, it is hoped that the community will have skills in processing seafood into modern food so that the products made can be sold and increase the income of the local community. Thus, the community will be better prepared to face the development of culinary tourism in Kurai Taji. The products made are expected to be an attraction for tourist visitors and improve the economy of the surrounding community.